Enthalpy-driven selective loading of CdSe0.75S0.25 nanoalloys in triblock copolymer polystyrene-b-polyisoprene-b-polystyrene. (September 2016) - Aşkın, Görkem; Çeçen, Volkan; Ünlütürk, Seçil Sevim; Özçelik, Serdar; Demir, Mustafa M.
Graphical abstract: Highlights: CdSe0.75 S0.25 nanoalloys were associated with assymmetric triblock copolymer (PS-SIS). The nanoalloys with12 nm diameter were capped by different ligands (OA and TOPO). Depending on the ligand, placement of the nanoalloys in PS-SIS can be controlled. Abstract: CdSe0.75 S0.25 nanoalloys were blended with asymmetric triblock copolymer of polystyrene-b-polyisoprene-b-polystyrene(PS-SIS) in tetrahydrofuran. The fraction of styrene block varies from 14 to 22% with respect to isoprene by mass. The morphology of the copolymer cast film experiences a phase change from cylinder to lamella. CdSe0.75 S0.25 nanoalloys were prepared by two-phase method. The surface of the nanoalloys was capped by either oleic acid (OA) or n -tri-octylphosphonic acid (TOPO) in situ. The mean diameter of the alloyed particles is around 12 nm in both systems. The chemical nature of the nanoalloy surface was found to influence the dispersion of the particles over polymer volume. The size of the nanoalloy domains in PS is 50 nm, on average, consisting of approximately 0.7 wt% nanoalloys. However, the size of the nanoalloy domains is smaller when they are loaded into PS-SIS. The structure formation is predominantly determined by enthalpic compatibilization. Atomic force microscopy results suggest that the nanoalloys capped with TOPO sequester into PS-rich domains and enlarge the domain. On the other hand, the ones capped with OA prefer to locate in polyisoprene domains. The increase of particles over 1.0 wt% distorts the lamella structure.